2008
DOI: 10.2202/1553-3840.1164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Argan Oil on Platelet Aggregation and Bleeding Time: A Beneficial Nutritional Property

Abstract: Platelet hyperactivity is one of the most important factors responsible for thrombosis and incidence of cardiovascular diseases. In this study, we investigated the effect of argan oil (0.2, 0.5, 1 and 2 %) on blood platelet aggregation (in vitro and ex vivo) and on tail bleeding time (in vivo) on rats. The in vitro aggregation was monitored after pre-incubation of platelets with argan oil for one minute. The in vivo bleeding time and ex vivo aggregation were performed after 4 weeks of oral treatment (10 ml/Kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Indeed, Tian et al (2001) have shown that Lycopus lucidus fractions could inhibit rat platelet aggregation in vitro and mice platelet aggregation in vivo without affecting bleeding time. Recently, we have shown in our laboratory that rat chronic treatment by Argania spinosa oil despite the ex vivo anti-aggregant activity, did not affect tail bleeding time (Mekhfi et al, 2008). Moreover, Ferreira et al (1999) reported that, in spite of their anti-platelet effect, quinones isolated from Auxemma oncocalyx Taub.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, Tian et al (2001) have shown that Lycopus lucidus fractions could inhibit rat platelet aggregation in vitro and mice platelet aggregation in vivo without affecting bleeding time. Recently, we have shown in our laboratory that rat chronic treatment by Argania spinosa oil despite the ex vivo anti-aggregant activity, did not affect tail bleeding time (Mekhfi et al, 2008). Moreover, Ferreira et al (1999) reported that, in spite of their anti-platelet effect, quinones isolated from Auxemma oncocalyx Taub.…”
Section: Discussionmentioning
confidence: 90%
“…The concomittant presence of these chemicals is responsible for the cardioprotective and hypocholesterolemic properties of argan oil 7. Other major pharmacological properties of argan oil are still regularly reported 8–11. Noteworthingly, olive, almond, and argan oil share some similarities: they are all cold‐press oils, they are all produced from a tree fruit, they all contain at least 80% of unsaturated fatty acids 12, 13, oleic and linoleic acids are the two main unsaturated fatty acids of each oil while palmitic and stearic acids are the two main saturated fatty acids for each oil 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Both oils are rich in unsaturated fatty acids (Table 1) and general considerations regarding their respective advantages as edible oils have recently been reported [9,10]. Argan oil, whose fame is more recent than that of olive oil, has become the topic of intensive biological research and its pharmacological properties are currently actively being investigated on animal models [11][12][13] and in humans [14][15][16][17].…”
mentioning
confidence: 99%